NAFLD in Cardiovascular Diseases: A Contributor or Comorbidity? - Chen, Bing; Tang, W.H. Wilson; Rodriguez, Mario; Corey, Kathleen E.; Sanyal, Arun J.; Kamath, Patrick S.; Bozkurt, Biykem; Virk, Hafeez Ul Hassan; Pressman, Gregg S.; Lazarus, Jeffrey V.; El-Serag, Hashem B.; Krittanawong, Chayakrit (Seminars in Liver Disease, 2022)
Nonalcoholic fatty liver disease (NAFLD) and cardiovascular diseases are both highly prevalent conditions around the world, and emerging data have shown an association between them. This review found several longitudinal and cross-sectional studies showing that NAFLD was associated with coronary artery disease, cardiac remodeling, aortic valve remodeling, mitral annulus valve calcifications, diabetic cardiomyopathy, diastolic cardiac dysfunction, arrhythmias, and stroke. Although the specific underlying mechanisms are not clear, many hypotheses have been suggested, including that metabolic syndrome might act as an upstream metabolic defect, leading to end-organ manifestations in both the heart and liver. Management of NAFLD includes weight loss through lifestyle interventions or bariatric surgery, and pharmacological interventions, often targeting comorbidities. Although there are no Food and Drug Administration–approved nonalcoholic steatohepatitis-specific therapies, several drug candidates have demonstrated effect in the improvement in fibrosis or nonalcoholic steatohepatitis resolution. Further studies are needed to assess the effect of those interventions on cardiovascular outcomes, the major cause of mortality in patients with NAFLD. In conclusion, a more comprehensive, multidisciplinary approach to diagnosis and management of patients with NAFLD and cardiovascular diseases is needed to optimize clinical outcomes.
Keywords: nonalcoholic fatty liver disease; nonalcoholic steatohepatitis; cardiovascular diseases; coronary artery disease; heart failure